The journey towards Indonesian democracy: The concept of education in the view of Mohammad Hatta - Nur Rizkia; Nadra, Noni; Farha, Farha; Salina, Wilda; Putra, Wahyu Setya Purnama (Arshaka: Social Sciences and Education, 2025)
This study aims to analyze the concept of education in Mohammad Hatta's thinking as the foundation of democracy and explore its relevance to the contemporary Indonesian education system. The research method employs a qualitative literature review approach, analyzing journal articles as primary sources and books and historical documents as secondary sources using Miles et al.'s (2014) analysis technique, which includes data reduction, data presentation, and data verification.The research findings indicate that Mohammad Hatta's concept of education has holistic, transformative, and democratic characteristics with five main dimensions: education as a tool for liberation, character and morality building, a means of economic empowerment, a medium for leadership regeneration, and an instrument of social transformation. This concept emphasizes not only cognitive-intellectual aspects but also spiritual, social, and moral dimensions as the foundation of a democratic and socially just society. The findings demonstrate strong relevance to Indonesia's contemporary education system, particularly the philosophy of the Merdeka Curriculum and the Pancasila Student Profile Strengthening Program (P5). Limitations of the study include reliance on secondary sources, a narrow focus on the Indonesian context, and the failure to explore critical aspects of implementation in the digital age.